2019
DOI: 10.1111/eos.12659
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength between dentine and a novel fast‐setting calcium silicate cement with fluoride

Abstract: Bond strength between dentine and a novel fast-setting calcium silicate cement with fluoride Ranjkesh B, Kopperud HM, Kopperud SE, Løvschall H. Bond strength between dentine and a novel fast-setting calcium silicate cement with fluoride. Eur J Oral Sci 2019; 127: 564-569. © 2019 Eur J Oral SciThe aim of this study was to evaluate the dentine bond strength of a novel fast-setting calcium silicate cement (Protooth) versus a calcium hydroxide-based cement (Dycal), a calcium silicate cement (ProRoot MTA), and a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The Ca(OH) 2 paste remnants influenced only the bond strength of AH Plus sealer, which in the absence of the Ca(OH) 2 paste in the control group resulted in higher bond strength values than SN, independent of the root third. Furthermore, the SN group presented lower Ca(OH) 2 removal from the root canal, regardless of the root third, and the remaining paste may have changed the interaction of this sealer with the root dentin due to the lower levels covalent bonds formation or root canal dentinal tubule penetration (25‐27), thereby justifying the results obtained. The bond strength values were similar in all cases, except for the middle third of SN, regardless of Ca(OH) 2 paste remnants with regard to the MTA Fillapex sealer.…”
Section: Discussionmentioning
confidence: 86%
“…The Ca(OH) 2 paste remnants influenced only the bond strength of AH Plus sealer, which in the absence of the Ca(OH) 2 paste in the control group resulted in higher bond strength values than SN, independent of the root third. Furthermore, the SN group presented lower Ca(OH) 2 removal from the root canal, regardless of the root third, and the remaining paste may have changed the interaction of this sealer with the root dentin due to the lower levels covalent bonds formation or root canal dentinal tubule penetration (25‐27), thereby justifying the results obtained. The bond strength values were similar in all cases, except for the middle third of SN, regardless of Ca(OH) 2 paste remnants with regard to the MTA Fillapex sealer.…”
Section: Discussionmentioning
confidence: 86%
“…Studies demonstrated that innovated calcium silicate cement (Protooth) has improved diametral tensile strength in comparison to ProRoot MTA ( 19 ), and higher bonding ability to dentine compared to ProRoot MTA and glass ionomer cement ( 21 ). This supports the finding of the current study proposing an improvement on properties of the earlier generation of calcium silicate cement (ProRoot MTA) that would potentially match and exceed the bond strength of traditional zinc phosphate and glass ionomer cements.…”
Section: Discussionmentioning
confidence: 99%
“…The apatite-forming ability of calcium silicate cement contributes to biomineralization ( 20 ), dentine bonding enhancement ( 21 ), gap closure at the dentine-cement interface ( 20 ), and bacterial microleakage reduction ( 33 ). The presence of fluoride composition accelerates the apatite-forming ability of the cement ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations